2019
DOI: 10.1111/trf.15195
|View full text |Cite
|
Sign up to set email alerts
|

Aerial drones for blood delivery

Abstract: Aerial drone technology is now in use to improve medical care, especially blood delivery. The use of aerial drones is broader than just this and includes aerial photography, express shipping and delivery, disaster management, search and rescue operations, crop monitoring, weather tracking, law enforcement, and structural assessment. This wide use promises to accelerate and, ideally, reduce the cost of technological advances of drones. By doing so, drone use offers the opportunity of improving health care, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 6 publications
(10 reference statements)
1
35
0
2
Order By: Relevance
“…The Blood Cold Chain, Guide to the Selection and Procurement of Equipment and Accessories published by the World Health Organization guided our literature search. Our review of the literature within PubMed include MeSH terms in the following combinations: prehospital transfusion, prehospital blood, remote damage control resuscitation, austere blood, and austere transfusion 31 . We performed a search of the FDA Establishment Registration & Device Listing in the classification device name: warmer, blood.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Blood Cold Chain, Guide to the Selection and Procurement of Equipment and Accessories published by the World Health Organization guided our literature search. Our review of the literature within PubMed include MeSH terms in the following combinations: prehospital transfusion, prehospital blood, remote damage control resuscitation, austere blood, and austere transfusion 31 . We performed a search of the FDA Establishment Registration & Device Listing in the classification device name: warmer, blood.…”
Section: Methodsmentioning
confidence: 99%
“…Our review of the literature within PubMed include MeSH terms in the following combinations: prehospital transfusion, prehospital blood, remote damage control resuscitation, austere blood, and austere transfusion. 31 We performed a search of the FDA Establishment Registration & Device Listing in the classification device name: warmer, blood. For infusion devices, we searched the FDA Establishment Registration & Device Listing using the classification device name: infuser, pressure, for IV.…”
Section: Search Methodsmentioning
confidence: 99%
“…Historically, the development and acceleration of technology has been concentrated in HICs, despite evidence of rapid adoption and application of such technologies in LMICs; for example, the use of drones for blood delivery to remote hospitals, and electronic surveillance of childhood bacterial infections in Bangladesh. 45 , 46 …”
Section: Four Research Themesmentioning
confidence: 99%
“…Although our drone modelling suggests that the costs of today’s duplicated services may be reduced by mergers or improved transport, this cost reduction cannot be outweighed by the costs relating to purchasing, maintaining, and operating of UAVs and the required launch infrastructures. The current economy of complex drone transport is not known in detail sufficient for complete economic evaluation; however, studies have been published [ 8 , 43 ], and the history of technological development has demonstrated that the costs of technological innovations decline appreciably over time [ 44 , 45 ]. We did not focus on solutions that might minimize the total cost of transportation.…”
Section: Sustainability Of Future Drone Solutionsmentioning
confidence: 99%